Resistance to Pyrrolobenzodiazepine Dimers Is Associated with SLFN11 Downregulation and Can Be Reversed through Inhibition of ATR - Mao, Shenlan; Chaerkady, Raghothama; Yu, Wen; D’Angelo, Gina; Garcia, Andrew; Chen, Hong; Barrett, Allison M.; Phipps, Sandrina; Fleming, Ryan; Hess, Sonja; Koopmann, Jens-Oliver; Dimasi, Nazzareno; et al. (Molecular cancer therapeutics, 2021)
Resistance to antibody–drug conjugates (ADCs) has been observed in both preclinical models and clinical studies. However, mechanisms of resistance to pyrrolobenzodiazepine (PBD)-conjugated ADCs have not been well characterized and thus, this study was designed to investigate development of resistance to PBD dimer warheads and PBD-conjugated ADCs. We established a PBD-resistant cell line, 361-PBDr, by treating human breast cancer MDA-MB-361 cells with gradually increasing concentrations of SG3199, the PBD dimer released from the PBD drug-linker tesirine. 361-PBDr cells were over 20-fold less sensitive to SG3199 compared with parental cells and were cross-resistant to other PBD warhead and ADCs conjugated with PBDs. Proteomic profiling revealed that downregulation of Schlafen family member 11 (SLFN11), a putative DNA/RNA helicase, sensitizing cancer cells to DNA-damaging agents, was associated with PBD resistance. Confirmatory studies demonstrated that siRNA knockdown of SLFN11 in multiple tumor cell lines conferred reduced sensitivity to SG3199 and PBD-conjugated ADCs. Treatment with EPZ011989, an EZH2 inhibitor, derepressed SLFN11 expression in 361-PBDr and other SLFN11-deficient tumor cells, and increased sensitivity to PBD and PBD-conjugated ADCs, indicating that the suppression of SLFN11 expression is associated with histone methylation as reported. Moreover, we demonstrated that combining an ataxia telangiectasia and Rad3-related protein (ATR) inhibitor, AZD6738, with SG3199 or PBD-based ADCs led to synergistic cytotoxicity in either resistant 361-PBDr cells or cells that SLFN11 was knocked down via siRNA. Collectively, these data provide insights into potential development of resistance to PBDs and PBD-conjugated ADCs, and more importantly, inform strategy development to overcome such resistance.